Enhancing thermoelectric properties of n-type Bi2Te2.55Se0.45 through the incorporation of MXene nanosheets - Farah M. El-Makaty (14157090) (2025)
This paper investigates the impact of incorporating two-dimensional MXene (specifically Ti3C2) into n-type Bi2Te2.55Se0.45 alloys using ball-milling and hot-pressing techniques. The thermoelectric properties of various MXene contents (0.01, 0.05, 0.5, 1, 2, 3, and 4 Wt%) in the nanocomposite were explored. The synthesized 2 wt% MXene-Bi2Te2.55Se0.45 nanocomposite exhibited an average grain size of 74 ± 25 nm. The X-ray diffraction (XRD) and Transmission Electron Microscopy (TEM) analysis have confirmed the insolubility of MXene within the Bi2Te2.55Se0.45 matrix, establishing its presence as a nanofiller. TEM results further revealed a homogenous dispersion of MXene as multilayer nanoparticles, which are 50 to 100 nm in size. Measuring the thermoelectric properties of the prepared nanocomposites showed that the incorporation of MXene improved the charge transport properties–but only at low concentrations (0.01 wt%). The calculated ZT profile of this sample reached 0.84 at 150°C, resulting in 11 % improvements compared to the pristine Bi2Te2.55Se0.45 pellet at the same temperature. Other Information Published in: Materials Characterization License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.matchar.2025.115468